Report of a Working Group on Barley: Fifth meeting, 10-12 July 1997, Alterode/Gatersleben, Germany - Maggioni, L.; Knüpffer, H.; Bothmer, R. von; Ambrose, M.; Hammer, K.; Lipman, E.; International Plant Genetic Resources Institute; European Cooperative Programme for Plant Genetic Resources (1999)
These proceedings outline the discussions and recommendations made at the working group and contains the collection of presented papers from the meeting. Main topics of discussion include the European Barley Database (EBDB), the status of national collections, sharing responsibilities for conservation and promoting the use of barley genetic resources.